Comparison of Initial Outcome between Hand Assisted Laparoscopic Surgery and Laparoscopic Assisted Surgery for Colorectal Cancer at Maharaj Nakorn Chiangmai Hospital - Sutharat, Pawit; Siriwittayakorn, Paisit; Sandhu, Trichak (The Thai Journal of Surgery, 2010)
Objective: This study aimed to compare the initial outcome between hand-assisted laparoscopic surgery and laparoscopic assisted surgery in patients with colorectal cancer at Maharaj Nakorn Chiang Mai Hospital, Chiangmai,Thailand. Patients and Methods: Between June 2007 and January 2008, 10 patients underwent laparoscopic colorectal cancer surgery at our hospital. The information including history, clinical presentation, laboratory tests, radiological reports, operative findings, postoperative complications and length of hospital stay were recorded. Results: There were 5 patients in hand-assisted laparoscopic surgery group and another 5 patients in laparoscopic assisted surgery group. There were no significant difference between two groups in terms of operative time, total blood loss, post-operative pain score and length of hospital stay. There was no conversion to open surgery and no postoperative mortality. One postoperative complication with pneumonia occurred in laparoscopic assisted surgery group. Conclusions: Our initial experience showed that laparoscopic surgery for colorectal cancer was safe. There was no difference in term of initial outcomes between hand-assisted laparoscopic colectomy and laparoscopic assisted colectomy. However, more cases are needed before any solid conclusion can be drawn.